Solution-processed thickness engineering of tellurene for field-effect transistors and polarized infrared photodetectors - Chen, Fangfang; Cao, Dingwen; Li, Juanjuan; Yan, Yong; Wu, Di; Zhang, Cheng; Gao, Lenan; Guo, Zhaowei; Ma, Shihong; Yu, Huihui; Lin, Pei (Frontiers in Chemistry, 2022)
Research on elemental 2D materials has been experiencing a renaissance in the past few years. Of particular interest is tellurium (Te), which possesses many exceptional properties for nanoelectronics, photonics, and beyond. Nevertheless, the lack of a scalable approach for the thickness engineering and the local properties modulation remains a major obstacle to unleashing its full device potential. Herein, a solution-processed oxidative etching strategy for post-growth thickness engineering is proposed by leveraging the moderate chemical reactivity of Te. Large-area ultrathin nanosheets with well-preserved morphologies could be readily obtained with appropriate oxidizing agents, such as HNO2, H2O2, and KMNO4. Compared with the conventional physical thinning approaches, this method exhibits critical merits of high efficiency, easy scalability, and the capability of site-specific thickness patterning. The thickness reduction leads to substantially improved gate tunability of field-effect transistors with an enhanced current switching ratio of ~103, promoting the applications of Te in future logic electronics. The response spectrum of Te phototransistors covers the full range of short-wave infrared wavelength (1-3 μm), and the room-temperature responsivity and detectivity reach 0.96 AW-1 and 2.2×109 Jones at the telecom wavelength of 1.55 μm, together with a favorable photocurrent anisotropic ratio of ~2.9. Our study offers a new approach to tackling the thickness engineering issue for solution-grown Te, which could help realize the full device potential of this emerging p-type 2D material.